Simultaneous Multislice for Accelerating Diffusion MRI in Clinical Neuroradiology Protocols - Hoch, M.J.; Bruno, M.; Pacione, D.; Lui, Y.W.; Fieremans, E.; Shepherd, T.M. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Diffusion MR imaging sequences essential for clinical neuroradiology imaging protocols may be accelerated with simultaneous multislice acquisitions. We tested whether simultaneous multislice–accelerated diffusion data were clinically equivalent to standard acquisitions.MATERIALS AND METHODS: In this retrospective study, clinical diffusion sequences obtained before and after implementation of 2-slice simultaneous multislice acceleration and an altered diffusion gradient sampling scheme using the same 3T MRI scanner and 20-channel coil (n = 25 per group) were independently and blindly evaluated by 2 neuroradiologists for perceived quality, artifacts, and overall diagnostic utility. Diffusion tractography was performed in 13 patients both with and without 2-slice simultaneous multislice acceleration (b = 0, 1000, 2000 s/mm2; 60 directions). The corticospinal tract and arcuate fasciculus ipsilateral to the lesion were generated using the same ROIs and then blindly assessed by a neurosurgeon for anatomic fidelity, perceived quality, and impact on surgical management. Tract volumes were compared for spatial overlap.RESULTS: Two-slice simultaneous multislice diffusion reduced acquisition times from 141 to 45 seconds for routine diffusion and from 7.5 to 5.9 minutes for diffusion tractography using 3T MR imaging. The simultaneous multislice–accelerated diffusion sequence was rated equivalent for diagnostic utility despite reductions to perceived image quality. Simultaneous multislice–accelerated diffusion tractography was rated clinically equivalent. Dice similarity coefficients between routine and simultaneous multislice–generated corticospinal tract and arcuate fasciculus tract volumes were 0.78 (SD, 0.03) and 0.71 (SD, 0.05), respectively.CONCLUSIONS: Two-slice simultaneous multislice diffusion appeared clinically equivalent for standard acquisitions and diffusion tractography. Simultaneous multislice makes it feasible to acquire higher angular and q-space-resolution diffusion acquisitions required for translating advanced diffusion models into clinical practice.AFarcuate fasciculusCSTcorticospinal tractDSCDice similarity coefficientFAfractional anisotropyGRAPPAgeneralized autocalibrating partially parallel acquisitionSMSsimultaneous multislice